Analisis Urgensi Pembelajaran Berdiferensiasi Dalam Menciptakan Lingkungan Belajar Inklusif - Helmalia Fitri Atikah, Aisyah Nur Fairus , Diva Anzani (STKIP Paris Barantai, 2024)
Differentiated learning has become an effective strategy for creating an inclusive learning environment where every student has the same opportunity to develop. This research uses literature research methods to determine the urgency and impact of different learning approaches in creating an inclusive learning environment. The results of the analysis show that differentiated learning provides opportunities for each student to learn at a level that suits their learning needs. Differentiated learning allows student to work with relevant, challenging material and provides the support and guidance needed to achieve success. By using differentiated education in learning, educators can increase learning effectiveness, promote student engagment, and achieve better inclusive education.